Electrochemical Behavior of the Ni3Al Intermetallic Alloy in Nitrate Salts - Daniel Lopez-Dominguez; Nestor Belisario Gomez-Guzman; Cinthya Dinorah Arrieta-Gonzalez; Jonathan de la Vega Olivas; Jose Gonzalo Gonzalez-Rodriguez; Jesus Porcayo-Calderon; Jose Guadalupe Chacon-Nava (Metals)
In this paper, the electrochemical performance of the NiAl intermetallic immersed in the 60% NaNO3-40% KNO3 (wt%) eutectic mixture, also known as Solar Salt, is reported. Mass loss measurements and electrochemical tests evaluate its behavior at different temperatures (300, 400, and 500 °C). Mass loss measurements are performed over 1000 h, and electrochemical tests over 100 h. The mass loss results show that the Ni3Al intermetallic exhibits excellent corrosion resistance under the test conditions. Electrochemical measurements confirm the excellent performance of the Ni3Al intermetallic in molten solar salt in the test temperature range. Experimental observations show that increasing temperature decreases the corrosion resistance of the intermetallic and favors the formation of protective layers of the Al2O3 and NaAlO2 types.